Identification of gamma-glutamyl phosphate in the alpha 2 chains of chicken bone collagen. - Cohen-Solal, L (1979)
Purified components of chicken bone collagen contain approximately 4 atoms of organic phosphorus per mol of collagen, located principally in the alpha 2 chains. Previous analyses have demonstrated the absence of O-phosphoserine, O-phosphothreonine, and other phosphorylated hydroxy amino acids, phosphoamidated amino acids, and phosphorylated sugars. In the present report we establish that chicken bone collagen contains gamma-glutamyl phosphate. This was accomplished by the isolation of tritiated alpha-amino-delta-hydroxyvaleric acid after reductive cleavage with NaB[3H]H4 of the gamma components, the alpha 2 chains, and peptides enriched in organic phosphorus that were derived from the alpha 2 chains. Tritiated alpha-amino-delta-hydroxyvaleric acid was not detected in any of the following unphosphorylated proteins after cleavage with NaB[3H]H4:albumin and lysozyme, the alpha 2 chains of several unmineralized tissues, and, most importantly, dephosphorylated alpha 2 chains of chicken bone collagen. The alpha 2 chain of chicken bone collagen is the first structural protein found to contain an acyl phosphate.